COVID-19 Prevention Practices for Employees who Work From Office (WFO) - Evicenna Naftuchah Riani; Ratih Indraswari (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2021)
Background: COVID-19 pandemic in Indonesia has not ended yet. Since the New Habit Adaptation, previously known as the New Normal, employees have started return to work in offices. At the end of July 2020, the addition of new cases received a large number of contributions from employees working in the office, raising a new cluster known as the office cluster. Objective: This study aimed to analyze the association between characteristics and practice of preventing the transmission of COVID-19 among employees in Purwokerto, Central Java. Methods:  This is a quantitative study with a cross-sectional design. Online data collection was conducted in early August 2020. The variables were the respondents’ characteristics (gender, age, occupation, and income) and the practice of COVID-19 prevention among employees in the office (wearing a mask, maintaining physical distance, handwashing, opening doors and windows for air circulation). Fifty-seven employees started working in offices in Purwokerto who were involved in this research. Results: Most respondents were adults (82.5%), women (70.2%), working as private employees (77.2%) with an income above the minimum wage (73.7%). Almost all respondents have widely adopted the practice of washing hands (86%) and using masks (98.2%) since the pandemic’s emergence. However, many employees were unable to perform physical distancing (26.3%), stayed away from the crowd (29.8%), opened workspace doors/windows (56.1%), and tried to work outdoor (86%). There is no association between characteristics and prevention practice. Private companies need to tighten their health protocols and monitoring. They should provide rewards and punishments for employees who did not obey the regulation. Also, local governments need to supervise all companies in their area to enforce health protocols seriously.